Security Attacks And Proposed Solutions In Internet Of Things (Iot) - Minahil Irfan , Irshad Ahmed Sumra , Ijaz Ahmad Awan , Khalid Mahmood , Muhammad Aaqib Javed , Muhammad Akram Mujahid , Naheed Akhtar (Migration Letters, 2024)
IoT is one of the key areas of future research due to its real time applications for industry. IoT Applications take more attention from industry and different projects are in progress for safety of end user in smart future. Security is one of hot research area in future applications of IoT and security and privacy playing a key role for implementation of applications in real time environment and ensure the end user privacy. In this paper, we will discuss the importance of security in different types of IoT applications and discussed the security on different levels like security issues on sensing layer, on network layer, middleware layer and application layer and then provide the best solution according to the recent research of different researchers IoT security using Blockchain and security on different Attacks. Smart Home and Smart City are two major applications of IoT and end users are more concern about their privacy of data and successful implementation of IoT applications require to develop the user trust in IoT applications.